Association between sleep characteristics and mild cognitive impairment in elderly people - An, C.; Yu, L.; Wang, L.; Jin, G.; Song, M.; Zhu, Q.; Jia, H.; Liu, K.; Wang, M.; Wang, X. (Нейрофизиология, 2014)
We compared the sleep quality indices between patients with mild cognitive impairment (MCI) and normal elderly subjects and analyzed the effects of sleep characteristics on cognitive functions. Cases of MCI patients (320 persons, MCI group) and 630 normal elderly with matched age, gender, and level of education (control group) were enrolled in this study. The Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep characteristics. The Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) were used to assess cognitive function. There were 110 (34.3%) and 170 (27%) cases with sleep disorders in the MCI and control groups, respectively (P < 0.01). There was a significant difference of total PQSI scores between the two groups, and the scores of sleep duration (factor III) and habitual sleep efficiency (factor IV) in the MCI group were significantly lower than those in the control group. Total PQSI scores negatively correlated with MoCA scores and MMSE scores. MoCA scores negatively correlated with scores of the sleep latency (factor II), sleep duration (factor III), and habitual sleep efficiency (factor IV), while MMSE scores negatively correlated with scores of factor III and factor IV. The scores of attention and calculation, reading and language understanding, and visuospatial function (MMSE), and also of visuospatial/executive function, attention, and clock-drawing test (MoCA) in MCI patients without sleep disorders were significantly higher than those in MCI patients with such disorders. The incidence of sleep disorders is higher in patients with MCI, compared with normal elderly. Effects of sleep disorders on cognitive functions are mainly reflected in the state of attention, and visuospatial/executive function. Ми порівнювали показники якості сну у пацієнтів з помірними когнітивними порушеннями (MCI) та літніх людей без таких розладів і аналізували впливи характеристик процесу сну на когнітивні функції. У дослідженні брали участь 320 пацієнтів групи MCI та 630 здорових літніх людей контрольної групи, в яких співпадали вік, стать та рівень освіти. Для оцінки якості сну використовували Пітсбургський індекс якості сну PSQI, а для оцінки статусу когнітивної сфери – системи MMSE та MoCA. У групах МСI та контролю було 110 (34.3 %) та 170 (27 %) випадків розладів сну (P < 0.01). Сумарні значення оцінок PSQI демонстрували вірогідні міжгрупові відмінності; оцінки тривалості сну (фактор III) та звичайної ефективності сну (фактор IV) у групі MCI були вірогідно нижчими, ніж у контрольній групі. Загальні оцінки PSQI негативно корелювали з оцінками за шкалами MoCA та MMSE. Оцінки за MoCA негативно корелювали зі значеннями латентного періоду сну (фактор II), тривалості сну (фактор III) та звичайної ефективності сну (фактор IV), тоді як оцінки за MMSE знаходились у негативній кореляції з бальними оцінками факторів III та IV. Бальні оцінки за шкалами уваги, кількісних розрахунків, розуміння читання й мовлення та просторово-зорової функції за MMSE, а також просторово-зорової/виконавчої функції, уваги та тесту з малювання годинника за MoCA у пацієнтів групи MCI без розладів сну були істотно більшими, ніж відповідні значення у MCI-пацієнтів з такими розладами. Таким чином, частота розладів сну у пацієнтів із помірними розладами когнітивної сфери є вищою, ніж така у здорових літніх осіб. Впливи розладів сну на когнітивні функції в основному відображуються в розладах уваги та просторово-зорової/виконавчої функції.